The variability of antennal sensilla in Naucoridae (Heteroptera: Nepomorpha) - Agnieszka Nowińska (Nature Portfolio, 2021)
Abstract The morphology and distribution of sensilla on the surface of the antennae of the naucorids’ species were studied via scanning electron microscopy. Eleven types of sensilla were identified regarding specific sensory modalities, based on their cuticular morphology. Cuticle morphology identifies five types of sensilla trichodea, four types of sensilla basiconica, one type of sensillum coeloconicum and sensillum ampullaceum. Three new types of mechanosensitive sensilla were found. Moreover, the morphological diversity between the antennae allowed the distinction of ten different antennal types that correspond to different sensillar sets. The sensilla found in Naucoridae share similarities with the sensilla of other nepomorphan taxa, as well as of terrestrial insects. However, no sensillar synapomorphy was found between Naucoridae and Aphelocheiridae.